Fiberscopic Imaging of the Pediatric Nasopharynx. Issue 3 (1995) - Wang, Deyun; Clement, Peter
Abstract : This study describes the endoscopic findings about the size of the adenoid tissue and the condition of the nasopharyngeal orifice of the eustachian tube. Results confirmed that only fiberscopic examination allows a thorough inspection of the nasopharyngeal anatomy to make a correct diagnosis and design therapeutic planning. When the presence of adenoid hypertrophy resulting in nasal obstruction, snoring, and/or otitis media was confirmed endoscopically, adenoidectomy proved to be highly efficacious in relieving these symptoms.